EFFECTIVENESS OF INTERACTIVE LEARNING MULTIMEDIA FOR DIANA NORMAL DELIVERY CARE (MULTERIANA) ON IMPROVING STUDENTS' INTERESTS AND SKILLS - Nz.Gea, Diana Oktavia; Sutisna, Ma'mun; ,, Suparni; Herawati, Yanti; Wijayanegara, Hidayat; Rowawi, Roni (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
The learning process requires media that align with technological advancements to enhance effectiveness and innovation. One such tool is the MULTERIANA Application, designed to support improved learning outcomes. This study aimed to analyze the effectiveness of the MULTERIANA Application in increasing student interest and skills at the Harapan Keluarga Midwifery Academy. The research used a pre-experimental design with a one-group pretest-posttest approach. The population included all fourth-semester female students, with a total sample of 57 participants selected through total sampling. Data were analyzed using the Wilcoxon test. The results showed a significant effect of the MULTERIANA Application on student interest in learning APN (midwifery care in normal delivery), with a p-value of 0.000. Similarly, the application significantly improved students’ skills in practicing normal delivery care, also with a p-value of 0.000. Based on the WebQual 4.0 assessment, the application was rated 54.6% effective before the intervention and improved to 76.3% afterward, indicating enhanced effectiveness. In conclusion, the MULTERIANA Application successfully increased both interest and skills in midwifery students. It is recommended that this application be used as a learning medium in delivery care courses to help students practice APN more effectively and independently.